COMPETENCE-ACTIVE APPROACH AS A PEDAGOGICAL CONDITION OF THE FORMATION OF INFORMATION COMPETENCE ENGINEER TEACHERS (Journal of Information Technologies in Education (ITE), 2011)
The article discusses the implementation of competence-activity approach to the development of information competence of engineers and educators sewing profile as one of the most important pedagogical conditions.
Keywords: activity approach; pedagogical conditions of competence; the information competency engineer sewing teacher profile